PERAN MAHKAMAH KONSTITUSI DALAM PENYELESAIAN SENGKETA HASIL PILKADA 2024: ANALISIS TERHADAP AMBANG BATAS DAN PELANGGARAN TSM - Wijaya, Nasri; Muddin, Ahmad Ali; Pelu, Handika Dwi Ardiansyah; Pieter, Salvadoris; Rado, Rudini Hasyim (Astha Grafika, 2024)
Regional Head Elections (Pilkada) are a form of implementing direct democracy in Indonesia which provides space for the people to choose their leaders. However, in practice, disputes over regional election results often occur, either due to differences in vote results or serious violations that affect the election process. The Constitutional Court (MK) plays a strategic role in resolving regional election results disputes based on the provisions of Law Number 10 of 2016, especially Article 158 which regulates the threshold for vote differences and exceptions for structured, systematic and massive (TSM) violations. This research uses a normative juridical method with an analytical approach to statutory regulations, Constitutional Court decisions, and empirical data related to the 2024 Pilkada. The results of the research show that the application of the vote difference threshold provisions provides initial screening for incoming lawsuits, while proving TSM violations remains the main challenge due to the complexity of the evidence and political pressure. The conclusion of this research confirms that the role of the Constitutional Court is very important in maintaining the legitimacy of the regional election results and the integrity of the democratic process in Indonesia.